2012
DOI: 10.5194/cp-8-2039-2012
|View full text |Cite
|
Sign up to set email alerts
|

A re-evaluation of the palaeoclimatic significance of phosphorus variability in speleothems revealed by high-resolution synchrotron micro XRF mapping

Abstract: Abstract. Phosphorus (P) is potentially a very important environmental proxy in speleothem palaeoclimate reconstructions. However, the transfer of P to a speleothem seems to vary between cave sites. Therefore, it is important to investigate the source of P and the way it is incorporated into a speleothem on a site-by-site basis before it can be used as a robust palaeoclimate proxy.In this paper, the distribution of P in one modern and two Early Pliocene speleothems formed in coastal caves on Christmas Island (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 59 publications
3
37
0
Order By: Relevance
“…During dry episodes, speleothem surfaces are also more likely to be colonized by microbes as discussed by Frisia et al . () and this could explain the apparent correlation between fluorescence and Sr content.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…During dry episodes, speleothem surfaces are also more likely to be colonized by microbes as discussed by Frisia et al . () and this could explain the apparent correlation between fluorescence and Sr content.…”
Section: Discussionmentioning
confidence: 84%
“…The authors demonstrated that high Si/Ca content in the stalagmite coincides with more positive δ 18 O values and, thus, reduced rainfall amount. Furthermore, microbial mediation in silica precipitation cannot be entirely ruled out as amorphous silica was observed associated with micrite laminae in stalagmites from the Nullarbor (Australia) showing strong fluorescence and associated with S and P (Frisia et al ., ). Thus, the presence of intercrystalline silica may indicate microbial colonization of the coralloid surface, most likely when the surface of the speleothem was relatively dry.…”
Section: Discussionmentioning
confidence: 97%
“…In a pioneering study in SE Australia, McDonald et al (2007) presented 5-yrs of trace metal data from cave dripwater and noted a more complex response of dripwater Mg/Ca, Sr/Ca and Ba/Ca to climate than observed in temperate regions. More recently, Frisia et al (2012) demonstrated that the P record preserved in Australian speleothems could be both a function of within-cave microbial processes as well as soil-derived infiltration. However, despite these two studies, review of available literature indicate that karst infiltration processes in arid and semi-arid zones are rarely investigated and thus require further research.…”
Section: Introductionmentioning
confidence: 99%
“…An explanation proposed by Frisia et al (2012) is that P is not derived from soil leaching but from other sources such as phosphate minerals present in the epikarst or microbiological activity. However, no data are available on the P concentrations in the host rock and no microbially induced petrographic features were observed in the Proserpine speleothem, making it hard to test this hypothesis.…”
Section: Zinc Yttrium and Lead Proxiesmentioning
confidence: 99%